Pursuance of a passive filter for a multi-coil EV charger employing a solar connected system to enhance power quality - Saini, Manoj; Gautam, Desh Deepak; Saini, Sumit; Chaudhary, Sunil Kumar; Srivastava, Puneet Chandra; Srivastava, Kiran; Sharma, Amit Kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This study describes the use of a passive filter to enhance power quality (PQ) of a multi-coil charger for (EVs) using a solar connected system. Wireless charging solutions have been developed as a result of the rising demand for EVs, which use multi-coil chargers to transfer power wirelessly. However, the high-frequency switching used in these chargers can cause power quality issues, such as harmonic distortion, which can affect the performance of the EV and the grid. To reduce PQ incidence effect during charging, a MATLAB model has been created here. The proposed system provides an innovative approach to addressing power quality challenges associated with electric vehicle charging infrastructure. The integration of a passive filter for multi coil wireless power transfer (MCWPT) can significantly improve power quality and promote the use of clean energy in the transportation sector. This study contributes to the development of sustainable solutions for addressing the challenges associated with electric vehicle charging infrastructure.